Opening ceremony of the ANC Holland Solidarity Hospital in Mazimbu, refugee settlement of the ANC in Tanzania. Centre: Henk Odink, chairman of the Dutch Medical Committee Angola (MKA) which financed the building of the hospital
Opening ceremony of the ANC Holland Solidarity Hospital in Mazimbu, refugee settlement of the ANC in Tanzania. Centre: Henk Odink, chairman of the Dutch Medical Committee Angola (MKA) which financed the building of the hospital.